Representation of Friendship and Aggressive Behavior in Primary School Children - Di Norcia, Anna; Bombi, Anna Silvia; Pinto, Giuliana; Mascaro, Chiara; Cannoni, Eleonora (Frontiers in Psychology, 2022)
This study examines the representation of friendship during middle childhood, and its impact on aggressive behavior. The literature shows that friendship is almost a “gym of social skills”, which in turn are a protective factor against aggressive behavior; in this regard the quality of friendship is especially important, but this quality becomes less and less accessible to direct observation as children grow older and spend most of their time in the externally regulated environment of primary school. To assess friendship quality requires to allow children to present their own perspective on the relationship, a goal that we have tackled through drawing. Children 6 to11 years old were individually asked to draw themselves and a close friend in two situations (relational Wellbeing and relational Distress) and to complete a 20 item scale of Physical and Verbal Aggression. Data were analyzed with three main aims: 1) to show if and how the representation of two core features of relationships (relatedness and individuality) changes according the situation and/or according to children’s gender; 2) to focus on the representation of distressing situations to verify if they coincide with forms of conflict, and if they differ according to children’s gender; 3) to verify if the strength of indices of relatedness and individuality, both in situations of wellbeing and distress, predicts children’s tendency to enact aggressive behaviors. The results confirm that relatedness is the dominant feature of friendship, especially in situation of wellbeing, but also when the situation becomes distressing. Conflict is not always present when children don’t feel fine with their friend; boys and girls do not differ significantly in this regard, but they do differ in term of the management of relatedness and individuality when problematic situations arise . In line with previous studies, sex is a main predictor of aggressive behavior with peers, with boys more at risk than girls; however, the capacity to relate with one’s own friend even in difficult times (in which boys are not inferior to girls) predicts lesser aggression with peers in general.